Актуальные проблемы биоэтики: междисциплинарный подход - Буряк, В.В. (Культура народов Причерноморья, 2014)
Ускоренное развитие биотехнологий порождает комплексные вопросы на пересечении методологических и этических аспектов медицины, биотехнологий и философии. Биоэтические проблемы становятся весьма актуальными в поле междисциплинарного знания. Отмечено, что биоэтическая проблематика изначально носила междисциплинарный характер, поскольку была связана с пониманием места морального дискурса в биологии, где проявлена антропологическая тематика философского плана. Этические проблемы расширенного развития биотехнологий с необходимостью является предметом философов, биологов и историков науки. Показано, что педагогическая цель преподавания учебного курса заключается в обеспечении студентов различных специальностей, понимание специфики актуальных проблем биоэтики. В статье широко обсуждаются биоэтические, философские и междисциплинарные аспекты развития биотехнологий. Новизна исследования заключается в обсуждении и анализе различных аспектов междисциплинарного характера, эвристического поля где пересекаются различные познавательные подходы: биомедицины, биотехнологий, биоэтики и философии. Прискорений розвиток біотехнологій породжує комплексні питання на перетині методологічних і етичних аспектів медицини, біотехнологій і філософії. Біоетичні проблеми стають дуже актуальними в поле міждисциплінарного знання. Відзначено, що біоетична проблематика спочатку носила міждисциплінарний характер, оскільки була пов'язана з розумінням місця морального дискурсу в біології, де проявлена антропологічна тематика філософського плану. Етичні проблеми розширеного розвитку біотехнологій з необхідністю є предметом філософів, біологів та істориків науки. Показано, що педагогічна мета викладання навчального курсу полягає у забезпеченні студентів різних спеціальностей, розуміння специфіки актуальних проблем біоетики. У статті широко обговорюються біоетичні, філософські та міждисциплінарні аспекти розвитку біотехнологій. Новизна дослідження полягає в обговоренні та аналізі різних аспектів міждисциплінарного характеру, евристичного поля де перетинаються різні пізнавальні підходи: біомедицини, біотехнологій, біоетики і філософії. Accelerated development of biotechnology raises complex issues at the intersection of methodological and ethical aspects of medicine, biotechnology and philosophy. Bioethical issues are of great importance in the field of interdisciplinary knowledge. Noted that bioethical issues initially wore interdisciplinary nature, since it was linked to the understanding of the place of moral discourse in biology, which is manifested anthropological themes philosophical plane. Bioethical issues very relevant in the context of socio-humanitarian and philosophical studies. Key issues of bioethics and above were interdisciplinary in nature, because they were related to the functioning of ethical discourse in biology. It is shown that the pedagogical goal of teaching training course is to provide students from different disciplines, understanding the specifics of actual problems of bioethics. Ethical issues extended development of biotechnology is necessarily subject to the philosophers, biologists and historians of science. It is shown that the pedagogical goal of teaching training course is to provide students from different disciplines, understanding the specifics of actual problems of bioethics. The article widely discussed bioethical, philosophical and interdisciplinary aspects of biotechnology. The novelty of the research is to discuss and analyze different aspects of the interdisciplinary nature of the field of heuristic where different cognitive approaches: biomedicine, biotechnology, bioethics and philosophy.